Terrorism and the Pandemic - Gunaratna, Rohan; Petho-Kiss, Katalin (Berghahn Books, 2023)
Coronavirus, known officially as SARS-CoV-2 (COVID-19), is an evolving threat. Threat entities have explored and exploited the pandemic to advance their agenda. Although lockdowns inhibited virus attacks in government-controlled areas, terrorist attacks continued unabated in the conflict areas. While government entities and military forces abided by lockdown measures, postponing training and scaling down operations, insurgent and terrorist groups operated relatively freely and mounted attacks. Both on the battlefields and off the battlefields, threat groups have invested in digital acceleration, maintaining strength and ideological influence during COVID-19.